Biologia e uso de habitat por Gymnorhamphichthys rondoni (Rhamphichthyidae: Gymnotiformes) - Garcia, Elisa (Instituto Nacional de Pesquisas da Amazônia - INPA, 2020)
Gymnorhamphichthys rondoni is a small electric fish species (Gymnotiformes) that has a wide distribution in the Amazon. The fact of inhabiting small and shallow streams, as well as the habit of resting buried in the sand during the day, constitute very favorable characteristics for conducting ecological and behavioral studies under natural and laboratory conditions. However, little information is available on basic aspects of its biology and habitat use under natural conditions. This thesis presents new information on reproductive biology, sexual dimorphism and habitat use by a population of G. rondoni in a small “terra firme” (upland stream) in the Central Amazon. Spawning occurs mainly in the first half of the rainy season and is positively associated with the increase in the electrical conductivity of the water and the amount of suspended solids, and negatively with the dissolved oxygen content. The oocytes are proportionally large and relatively few, and the spawning was considered as synchronic in two groups. We found several young individuals concentrated in very small areas, which may indicate some form of aggregation motivated by microhabitat characteristics and/or gregarious habits. Still, the detection of a high proportion of young individuals coincided with the apparent disappearance of the adults in the section of igarapé studied. These evidences suggest that the species may exhibit what could be defined as "functional semelparity". In addition, G. rondoni presents sexual dimorphism related to the relative size of the head and the position of the urogenital papilla: males have a proportionally larger head, and females' papilla is horizontally elongated, larger than those of males and located in the vertical line below the eye, while male’s papilla is vertically elongated , smaller, and located in the vertical line below the opercular opening. As far as we know, this is the first record of sexual dimorphism in a species of Rhamphichthyidae, but the functional significance of these differences has not yet been elucidated. Regarding habitat use, we observed that individuals shows fidelity to its diurnal resting site; however, the location of resting individuals during the day could not be explained by the stream depth at the resting site or by the percentage of the bed covered by sand. In addition, we found that females move less than males, and males move as much as young individuals. This pattern indicates that males of G. rondoni probably search actively for a sexual partner while females would perform the sexual selection. Despite the advances in knowledge generated by this thesis, several questions about the ecology and behavior of this species remain open and should encourage future studies.